2018
DOI: 10.1021/acschemneuro.8b00294
|View full text |Cite
|
Sign up to set email alerts
|

DARK Classics in Chemical Neuroscience: Ibogaine

Abstract: The West African iboga plant has been used for centuries by the Bwiti and Mbiri tribes to induce hallucinations during religious ceremonies. Ibogaine, the principal alkaloid responsible for iboga's psychedelic properties, was isolated and sold as an antidepressant in France for decades before its adverse effects precipitated its removal from the market. An ibogaine resurgence in the 1960s was driven by U.S. heroin addicts who claimed that ibogaine cured their opiate addictions. Behavioral pharmacologic studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
40
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 93 publications
0
40
0
4
Order By: Relevance
“… 24 Ibogaine was used in France for over 30 years as an anti-depressant and a stimulant until the mid-1960s. 25 Ibogaine treatment is reported to alleviate a spectrum of mood and anxiety symptoms 25 28 and is associated with self-reported improvements in cognitive functioning in individuals with substance use disorders. 29 31 During treatment, ibogaine allows the evocation and reprocessing of traumatic memories and occasions therapeutic and meaningful visions of spiritual and autobiographical content, 26 , 29 , 30 , 32 which are of central relevance in addressing PTSD-related psychological content.…”
Section: Introductionmentioning
confidence: 99%
“… 24 Ibogaine was used in France for over 30 years as an anti-depressant and a stimulant until the mid-1960s. 25 Ibogaine treatment is reported to alleviate a spectrum of mood and anxiety symptoms 25 28 and is associated with self-reported improvements in cognitive functioning in individuals with substance use disorders. 29 31 During treatment, ibogaine allows the evocation and reprocessing of traumatic memories and occasions therapeutic and meaningful visions of spiritual and autobiographical content, 26 , 29 , 30 , 32 which are of central relevance in addressing PTSD-related psychological content.…”
Section: Introductionmentioning
confidence: 99%
“…Ibogaine is the main indole alkaloid isolated from the root bark of the African shrub Tabernanthe iboga (Figure 1). [1][2][3] It is considered an atypical psychedelic drug capable of inducing waking dream-like states (oneirogenic effects) and vivid memory recall and replay. 4,5 Anecdotal reports and open label case studies with volunteers seeking detoxification from heroin and cocaine indicated ibogaine's ability to interrupt the drug dependence phenotype via rapid and lasting relief of drug withdrawal symptoms and cravings.…”
Section: Introductionmentioning
confidence: 99%
“… The psychedelic alkaloid ibogaine has anti-addictive properties in both humans and animals. 1 Unlike most substance use disorder (SUD) medications, anecdotal reports suggest that ibogaine possesses the potential to treat patients addicted to a variety of substances including opiates, alcohol, and psychostimulants. Like other psychedelic compounds, its therapeutic effects are long-lasting, 2 which has been attributed to its ability to modify addiction-related neural circuitry through activation of neurotrophic factor signaling.…”
mentioning
confidence: 99%